(untitled) (Theatrum historiae, 2023)
Old maps and images – paintings, drawings, graphics, and, in recent centuries, old photographs and postcards – capture the space around us, the proverbial “stage of history”, and have been seen as lucrative antiques for ages. However, the beauty of the old original still has magic in the digital age because the appeal of the old “representations of the landscape” remains. This is true for 15th-century murals, 17th-century copper engravings, and 19th-century lithographs. The present article, despite (unavoidably) being based on a series of micro-examinations delineated by time, territory, and relations to individuals, families, or institutions, takes on the characteristics of an aggregated work. It is dedicated to “images of the cultural landscape” as a whole, their role when they were created, their uses for the people that ordered them, and their role today (in this case primarily as a historical source).